(untitled) (Journal of actual problems of jurisprudence, 2019)
According to the purpose of scientific work the legal characteristic of the financial exchange and securities market is given. It is considered features of the financial exchange and off-exchange the organizations, and also subjects of infrastructures of securities market. In research it is discussed functions of participants of securities market Keywords: securities market, primary and secondary market, financial exchange, security, issue security, professional participants, issuer.